1975
DOI: 10.1042/cs0490323
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight and Body Water in Chronic Cor Pulmonale

Abstract: 1. Body weight was measured through forty consecutive illnesses in seventeen patients with oedema in association with chronic bronchitis and hypoxia. All patients were taking diuretic drugs at the time. 2. Body weight increased little as peripheral oedema and a raised jugular venous pressure appeared. The subsequent weight-loss during treatment was usually greater than the pre-treatment weight-gain. Body weight increased slowly in convalescence to equal or exceed hospital admission weight without a deteriorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…This finding confirms that of Telfer and colleagues (1975), who found significantly higher values (an increase of 20%) at 48 hours than at 24 hours in similar patients, and suggests that apparent deficiencies of potassium derived from 24-hour values of Ke (Baum et al, 1959;Bauer et al, 1966;Telfer et al, 1968;Campbell et al, 1975) There remains an unexplained discrepancy between the gross potassium depletion reported (Schloerb et al, 1970;Telfer et al, 1975) at 48 hours after administration of 42K and our previous (Howie et al, 1976) and present findings. However, it is interesting to note in the study of Telfer et al (1975) that both the value of Ke at 48 hours per'litre of intracellular water and the volume of intracellular water were normal.…”
Section: Discussionsupporting
confidence: 84%
“…This finding confirms that of Telfer and colleagues (1975), who found significantly higher values (an increase of 20%) at 48 hours than at 24 hours in similar patients, and suggests that apparent deficiencies of potassium derived from 24-hour values of Ke (Baum et al, 1959;Bauer et al, 1966;Telfer et al, 1968;Campbell et al, 1975) There remains an unexplained discrepancy between the gross potassium depletion reported (Schloerb et al, 1970;Telfer et al, 1975) at 48 hours after administration of 42K and our previous (Howie et al, 1976) and present findings. However, it is interesting to note in the study of Telfer et al (1975) that both the value of Ke at 48 hours per'litre of intracellular water and the volume of intracellular water were normal.…”
Section: Discussionsupporting
confidence: 84%
“…For instance, CAMPBELL et al [8] found that exchangeable sodium was not only normal after treatment for oedema but also in two of three patients when gross oedema had developed again. This would mean that oedema formation is not, or at least not always, simply due to accumulation but rather to redistribution of fluid.…”
Section: Body Fluid Volumes In Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…The mechanisms by which patients with COPD retain salt and water are not completely understood. Little information is available on changes in body fluid volumes in patients with COPD, and the few available data are conflicting [112][113][114][115][116]. Although there is certainly volume excess at advanced stages when gross oedema is present, the extent to which expansion of the extracellular volume occurs at earlier stages is not clear.…”
Section: Disturbances In Fluid Homeostasismentioning
confidence: 96%